2013
DOI: 10.1002/ccd.24399
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for coronary artery bypass graft surgery or percutaneous intervention in multivessel coronary artery disease

Abstract: Objectives Determine if patients prefer multi-vessel percutaneous coronary intervention (mv-PCI) over coronary artery bypass graft surgery (CABG) for treatment of symptomatic multi-vessel coronary artery disease (mv-CAD) despite high 1-year risk. Background Patient risk perception and preference for CABG or mv-PCI to treat medically refractory mv-CAD is poorly understood. We hypothesize that patients prefer mv-PCI instead of CABG even when quoted high mv-PCI risk. Methods 585 patients and 31 physicians wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
3
32
1
3
Order By: Relevance
“…However, despite knowledge of greater repeat revascularization procedures and even mortality associated with PCI compared with CABG, patients still frequently prefer PCI over CABG because of the perceived less invasive nature of the PCI procedure and the quicker recovery post PCI. 44 In context of such complexities, decision making in this challenging group of patients with complex multivessel coronary artery disease should be reviewed in the framework of a Heart Team to define the optimal revascularization strategy for each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite knowledge of greater repeat revascularization procedures and even mortality associated with PCI compared with CABG, patients still frequently prefer PCI over CABG because of the perceived less invasive nature of the PCI procedure and the quicker recovery post PCI. 44 In context of such complexities, decision making in this challenging group of patients with complex multivessel coronary artery disease should be reviewed in the framework of a Heart Team to define the optimal revascularization strategy for each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in this field has explored potential limitations of composite endpoints in cardiovascular trials, demonstrating a large variation in the importance of the component end points [5,21] and differences in clinician and patient perception of certain end points [22]. Other studies have incorporated different novel methods (such as win ratio and Anderson-Gill recurrent events models) to reinterpret clinical trial data [23].…”
Section: Challenging the Use Of Composite Clinical Endpoints In Rctsmentioning
confidence: 99%
“…Although we did not formally assess the reasons why participants in our study opted for CABG or PCI, one can speculate that patients` perception of morbidity (eg sternotomy) and prolonged recovery associated with CABG might be an important factor to prefer staged PCI over CABG in our scenario. Kipp et al observed that patients' choice of revascularisation method was most influenced by the risk of death, and modestly influenced by risk of repeat procedure or stroke. This would explain at least in parts the fact, that even patients with optimal clinical results following CABG (the group of patients with ≥7 years without anginal symptoms) did not prefer CABG over PCI.…”
Section: Discussionmentioning
confidence: 99%